2020
DOI: 10.2217/cnc-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of ice hockey players after retirement due to concussions

Abstract: Background: Sports-related concussion (SRC) is increasingly recognized as a potential health problem in ice hockey. Quality of life (QoL) in players retiring due to SRC has not been thoroughly addressed. Materials & methods: QoL using the Sports Concussion Assessment Tool 5th Edition, Impact of Event Scale-Revised and Short Form Health Survey was measured in Swedish ice hockey players who retired due to persistence of postconcussion symptoms or fear of attaining additional SRC. Results: A total of 76 playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These findings support previous literature that have found physical pain to be associated with poor mental health 14,16 and reduced quality of life. 29,30 However, this study brings into question studies that conclude concussion is responsible for negative changes to mental health and quality of life, that do not account for physical pain. 3,4,7,8 As concussion and physical pain often co-exist, 9,10 it could be that previous studies have misattributed these negative consequences to concussion, where in fact physical pain may be the responsible factor.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These findings support previous literature that have found physical pain to be associated with poor mental health 14,16 and reduced quality of life. 29,30 However, this study brings into question studies that conclude concussion is responsible for negative changes to mental health and quality of life, that do not account for physical pain. 3,4,7,8 As concussion and physical pain often co-exist, 9,10 it could be that previous studies have misattributed these negative consequences to concussion, where in fact physical pain may be the responsible factor.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, physical pain was significantly associated with poor mental health and reduced quality of life, supporting previous literature that deems this to be the case. 29,30 The effect on quality of life was stronger than any effect on mental health measures, and just under twice as strong as the effect on trait-anxiety. Given what we know about the link between physical pain and depression, 14,16 and depression and quality of life, 59 it is sensible to treat them similarly.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The research group found that many players felt that they had lost their identity as a player, and often struggled to develop an off-the-ice persona or find other sources of meaning in their lives. Engstrom was also an author on our final paper, this time with lead author Anna Gard (Lund University, Sweden) and colleagues [ 7 ]. Again looking at retired hockey players, in this paper the group used the Sports Concussion Assessment Tool 5th Edition, the Impact of Event Scale-Revised and the Short Form Health Survey to measure the quality of life of players who had retired due to concussion.…”
Section: Content Highlights From 2020mentioning
confidence: 99%